Polskie partie liberalne wobec integracji Polski ze Wspólnotami Europejskimi/Unią Europejską (Świat Idei i Polityki, 2007)
The article brings up the issue of the attitude of the Polish liberal community towards integration with the European structures. Its objective is to show the attitudes, opinions and argumentation of the liberal pro-integrative option after the year 1989. In this regard, the standpoints of the following parties are analysed: Citizens' Movement for Democratic Action (ROAD), Democratic Union (UD), Liberal-Democratic Congress (KLD), Freedom Union (UW) and Civic Platform (PO). In further parts of the article, the author shows that to liberal parties Western Europe constituted a synonym of freedom, democracy, prosperity and progress. One can get an impression that this fascination was so strong that it was trusted without any critical reflections. As a result, the liberals contributed to the guiding of Poland's development, accepting the pro-western option that was maintained and consistently realised by all successive governments.URI